(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: Evaluation of the results of treating stillbirths after 24 weeks at Hanoi Obstetrics and Gynecology Hospital using internal medicine in 2023. Subjects and methods: Descriptive observational study based on medical records of 105 pregnant women with stillbirth after 24 weeks at Hanoi Obstetrics and Gynecology Hospital using internal medicine. Results: Among 105 pregnant women with intrauterine fetal demise induced medically, 67.6% received Misoprostol and 32.4% received Oxytocin. In the 71 patients induced with Misoprostol, 87.3% achieved successful labor, with the most common doses being 125-150 µg and 175-200 µg. Higher gestational age was associated with lower vaginal Misoprostol doses (p < 0.05). All pregnant women receiving Oxytocin achieved successful labor, with the most common dose of 10-20 IU. Labor was initiated within 24 hours in 46.9% of cases, and longer gestational age was associated with shorter labor duration (p < 0.05). Overall, 79% of cases had no complications; reported complications included hemorrhage (14.3%) and infection (6.7%). Conclusion: Misoprostol is the preferred choice over Oxytocin for induction of labor in stillbirths (67.6% vs. 32.4%), consistent with many other studies. Gestational age is an important role in influencing the type of drug, induction dose, and outcome of labor induction.